Analisis Penerapan Pengendalian Internal Persediaan dalam Pengelolaan Persediaan Barang Dagang (Studi Kasus pada Minimarket Indomaret PT Indomarco Prismatama) - Safitri, Ariska; Nasution, M. Irsan (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The purpose of this research is to understand the internal control system for merchandise inventory at Indomaret Minimarket. The issue faced by this company is the frequent loss of inventory. This type of research is descriptive research. The research method used is qualitative descriptive. Data collection was done through interviews and documentation. The data sources used primary data and secondary data. The results of this study indicate that the internal control system for merchandise inventory at Indomaret Minimarket has not been implemented well. Effective actions to minimize damage and loss of merchandise and to maintain inventory levels have not been carried out properly. The internal control system implemented by the company has not been running effectively and efficiently because there are several internal control elements that have not been functioning well, such as the lack of strict separation of stores, warehouse functions, and the examination of goods transactions that are implemented by only one function. Additionally, employee rotation has not been conducted periodically; in the Indomaret warehouses and stores, there are still some CCTV cameras that are blurry or even not working, and there is also no monitoring function aimed at observing consumers shopping in Indomaret stores so that they do not rotate employees periodically to anticipate theft and similar actions.